Nomads of the world - National Geographic Society (U.S.) Special Publications Division; Bahmanbegui, Mohammad; Cole, Donald P.; De Munck, Alyette; Dyson-Hudson, Neville; Englebert, Victor; McIntyre, Loren; Nimmo, H. Arlo; Ruhela, Satya Pal; Carmichael, Leonard; Allen, William L.; Taney, Joseph (Washington, D.C. National Geographic Society, 1971)
"Distinguished scholars write of the lives and customs of eight groups- Lohars of India, etc. who wander over long distances in search of food and water for their families and animals."
Nomadic peoples find freedom and identity in the life they follow -- Lohars : Bullock-cart blacksmiths of India's Rajasthan state -- Al Murrah Bedouin : "The Pure Ones" rove Arabia's empty sands -- Bajau : Gentle boat-dwellers of the Philippines -- Qashqa'i : Hardy shepherds build a new future in Iran -- Tuareg : Men of the veil, Women of ancient pride travel the Sahara -- Bambuti : Exuberant pygmies of Africa's Deep Ituri Forest -- Guajiros : Tough and touchy indians wander Colombian scrubland -- Bororos : Cattle herdsmen of Niger meet in the season of dances.
Includes bibliographical references and index.
Keywords: Nomads